Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan (Studi Pada Mahasiswa Pengguna Grab Di Fakultas Ekonomi Dan Bisnis Unisma) - Hamsan Rahmat; Muhammad Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of service quality, price and quality of information systems on Grab customer satisfaction. The population in this study are Grab customers at the Unisma Faculty of Economics and Business. The sample used is some students with the respondents being Grab customers. The technique used in sampling is a technique by using the selected sample is 67 respondents. Data was collected by using a questionnaire method. The data analysis method used is multiple regression analysis with the help of SPSS software version 14 (Statistical Products and Service Solutions version 14). The test data used are simultaneous hypothesis testing (f), coefficient of determination (R2), and partial hypothesis testing (t). The results showed that the independent variables simultaneously had a significant effect on the dependent variable. Based on the results of the coefficient of determination test, the Adjusted R value was obtained at 74.7%, while the remaining 25.3% was influenced by other variables not included in this study. Based on the partial test results, three variables affect customer satisfaction, service quality (sig = 0.045), price (sig = 0.005) and information system quality (sig = 0.030) affect customer satisfaction. Keywords: the effect of service quality and price on custumer satisfaction